새로운 크롬 화합물을 이용한 에틸렌 3량화 촉매 - 박동식 (The Graduate School, Ajou University, 2015)
The conventional Phillips ethylene trimerization catalyst prepared by reacting Cr(EH)3 (EH = 2-ethylhexanoate), 2,5-dimethylpyrrole (Me2C4H2NH), Et3Al, and Et2AlCl in an aromatic hydrocarbon solvent was rectified to a congener composed of a new chromium precursor (EH)2CrOH, (Me2C4H2N)AlEt2, and Et3Al•ClAlEt2. Reaction of CrCl3 with 3 equiv Na(EH) in water did not generate Cr(EH)3, but unexpectedly produced (EH)2CrOH. In comparison with the erratic catalytic performance of the original Phillips system due to ill-defined nature of the Cr(EH)3 source (16 or 6.8  106 g/mol-Cr•h depending on the source), the rectified system exhibited consistently high activity (54  106 g/mol-Cr•h). Solution structure of (EH)2CrOH was inferred to be an adamantane skeleton composed of four (EH)2CrOH units and two water molecules (6) based on the cryoscopy measurement of the molecular weight and the revealed crystal structure of a side product: a tetranuclear chromium(III) cluster (5) coordinated by three 3-CH2 , one 2-CH3, two 2-OH, and three (5-Me2C4H2N)AlMe2Cl ligands. Reaction of (EH)2CrOH with Me2AlCl in benzene afforded precipitates of MeCrCl2, the structure of which was revealed as a THF adduct: MeCrCl2(THF)3. Reaction of (EH)2CrOH with (Me2C4H2N)AlMe2•OEt2 afforded the dimeric Cr(II)-complex (3) coordinated by (5-Me2C4H2N)AlMe2(NC4H2Me2) and 2-1:2-Me2C4H2N ligands. 3 provided highly active species when activated with Et3Al•ClAlEt2, indicating that it was a key intermediate in the Phillips catalyst preparation.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2015. 2
Keywords: 에틸렌; 삼량화; ethylene; trimerization